RESPONSE OF AN IDEOTYPE OF CLUSTER ONION (ALLIUM CEPA L. VAR. AGGREGATUM) TO FARM AND ANIMAL WASTES - C.T. SATHAPPAN, D. STELLA, D. ANBARASI, K. HARIPRIYA (Journal of Phytology, 2018)
In Tamilnadu, Ariyalur district contributes a major share of cluster onion production. An ideotype popular among the growers of this locality is preferred by consumers of entire state for its size, storability and taste. Hence the present investigation was carried out the in a farmer’s field at Vennallur located in Ariyalur District during 2017. The experiment was laid out with seven treatments in randomized block design. Each treatment was replicated thrice. The treatments included three kinds of practices adopted by the farmers of the tract and four others where bulky organic manures (Vermicompost, Poultry manure) and concentrated organic manures (Neem cake and Groundnut cake) were substituted on ‘N’ equivalent basis, along with biofertilizers (Azospirillum and Phosphobacteria) and foliar spray of Panchakavya (3%). All the four treatments with organic inputs (T4 to T7) gave better results, when compared to farmer’s practice (T1 and T2). Though T3 was the best, incorporation of Poultry manure+Neem cake (T6) and Poultry manure+Groundnut cake (T7) along with Biofertilizer+Panchakavya 3 % improved the yield significantly in order.